Continuous flow biocatalysis: production and in-line purification of amines by immobilised transaminase from Halomonas elongata - Planchestainer, Matteo; Contente, Martina Letizia; Cassidy, Jennifer; Molinari, Francesco; Tamborini, Lucia; Paradisi, Francesca (Royal Society of Chemistry, 2017)
The continuous flow synthesis of a series of amines was successfully achieved by exploiting the enhanced stability and broad substrate scope of an immobilised transaminases from Halomonas elongata (HEWT). A series of substrates were tested in flow reactors and transformed to the corresponding amines in good to excellent yields. The process was implemented with an integrated in-line purification step for the recovery of the pure amines.